SEGMENTATION OF ONLINE FRESH PRODUCTSâ CONSUMERS BASED ON INTENTIONS AS THE BASIS FOR DETERMINING TARGET MARKET AND AGRIPEDIAâS PROMOTION STRATEGIES - Vindyasari, Muthia
The increase of technology users has caused a shift in patterns of offline shopping behavior to online shopping. In the past two years, online purchases of fresh food have raised by 15% globally. Agripedia, an online grocery platform selling fresh products in Indonesia, has a problem pertinent to declining in sales. This caused by promotional activities that did not run effectively. The promoters believe they did not understand Agripedia's target customers thus far. To increase the effectiveness of promotional activities, many companies have adopted target marketing. This approach will also be adopted in this study. Generally, target marketing begins by identifying the needs of each different customer segment. Then, the company decides one or more target market segments to be selected. For each segment, the fittest promotion strategy is established. Hopefully, it will increase marketing effectiveness. This study uses structural equation modeling and latent class cluster methods to form market segments based on factors that influence purchase intentions. The model used in the study was adopted from The Theory of Planned Behavior (TPB) and The Technology Acceptance Model. In this study, 9 main hypotheses are formed from the relationship between the 7 constructs used. Then, the formation of the latent class analysis model formed 5 additional hypotheses based on the relationship between covariate variables and latent constructs. The number of final samples used in the study was 278 people. There are three segments formed, namely "The Loyalist", "Convenience Seeker", and "Mature Traditionalist". The "The Loyalist" and "Mature Traditionalist" segments are then decided to be the target market. The findings in this study will be used as a recommendation to establish a promotional strategy based on factors that influence buying intentions in both target market segments.